A protein-enriched low glycemic index diet with omega-3 polyunsaturated fatty acid supplementation exerts beneficial effects on metabolic control in type 2 diabetes - Moosheer, Simone M. (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2014)
The current study aims to investigate practicability and effects of a combined dietary intervention with increased relative protein content supplemented with omega-3 polyunsaturated fatty acids (PUFA) on metabolic control and inflammatory parameters in a real life situation in type 2 diabetes patients.